The initial steps of biogenesis of cyanobacterial photosystems occur in plasma membranes - Zak, Elena (The National Academy of Sciences, 2001)
During oxygenic photosynthesis in cyanobacteria and chloroplasts of plants and eukaryotic algae, conversion of light energy to biologically useful chemical energy occurs in the specialized thylakoid membranes. Light-induced charge separation at the reaction centers of photosystems I and II, two multisubunit pigment-protein complexes in the thylakoid membranes, energetically drive sequential photosynthetic electron transfer reactions in this membrane system. In general, in the prokaryotic cyanobacterial cells, the thylakoid membrane is distinctly different from the plasma membrane. We have recently developed a two-dimensional separation procedure to purify thylakoid and plasma membranes from the genetically widely studied cyanobacterium Synechocystis sp. PCC 6803. Immunoblotting analysis demonstrated that the purified plasma membrane contained a number of protein components closely associated with the reaction centers of both photosystems. Moreover, these proteins were assembled in the plasma membrane as chlorophyll-containing multiprotein complexes, as evidenced from nondenaturing green gel and low-temperature fluorescence spectroscopy data. Furthermore, electron paramagnetic resonance spectroscopic analysis showed that in the partially assembled photosystem I core complex in the plasma membrane, the P700 reaction center was capable of undergoing light-induced charge separation. Based on these data, we propose that the plasma membrane, and not the thylakoid membrane, is the site for a number of the early steps of biogenesis of the photosynthetic reaction center complexes in these cyanobacterial cells.